1968
DOI: 10.1002/jlac.19687150110
|View full text |Cite
|
Sign up to set email alerts
|

Zur Stokvis‐Reaktion, XVII1) Vilsmeier‐Reaktion mit Pyrrol‐ und Pyrrolon‐Derivaten

Abstract: Pyrrole mit freier α‐Stellung ergeben bei der Vilsmeier‐Formylierung α‐Formylpyrrole. Besitzt das Ausgangspyrrol oder ‐pyrrolon einen Acetyl‐Substituenten, so entstehen bevorzugt Halogenacroleine 1 oder 2. Δ3‐Pyrrolone geben über Immoniumsalze 4 und innere Immoniumsalze 5 α‐Halogen‐α‐formylpyrrole 3, die sich reduktiv in Formylpyrrole überführen lassen. Am N nicht‐substituierte Bromformylpyrrole kondensieren mit Pyrrolonen in Zn/Natronlauge zu α‐Oxo‐dipyrromethenen (“Neo‐Typ”). – Durch Verwendung von Oxalylchl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1969
1969
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Under the influence of the Vilsmeier complex the N-unsubstituted 3,4-dimethylpyrrol-2-one 20 gives a good yield of the immonium salt 20a, the alkaline hydrolysis of which gives 2-formyl-5-chloropyrrole 21 [59][60][61]. N-Substituted pyrrol-2-ones dimerize with N-R-pyrrolid-2-ones during the action of protic and aprotic acids with yields of up to 79% [63].…”
Section: Pocl 3 Naohmentioning
confidence: 98%
“…Under the influence of the Vilsmeier complex the N-unsubstituted 3,4-dimethylpyrrol-2-one 20 gives a good yield of the immonium salt 20a, the alkaline hydrolysis of which gives 2-formyl-5-chloropyrrole 21 [59][60][61]. N-Substituted pyrrol-2-ones dimerize with N-R-pyrrolid-2-ones during the action of protic and aprotic acids with yields of up to 79% [63].…”
Section: Pocl 3 Naohmentioning
confidence: 98%
“…The most widely studied class consists of those congeners that are push-pull stabilized (10,11,13,14) and contain one to three electron-attracting substituents at C-2,4. Compounds 3a-e are examples of this type.…”
Section: Some Properties Of 6-dialkylamino-1-azafulvenesmentioning
confidence: 99%
“…Such compounds have also been obtained by the sodium hydride deprotonation of the diand tribromination products of the ternary iminium perchlorates derived from pyrrole-2-carboxaldehyde (1 1). von Dobeneck and co-workers (10) showed that these azafulvenes were particularly susceptible to nucleophilic addition at C-6, undergoing a variety of addition elimination reactions7 including hydrolysis to the corresponding aldehydes. We recognized that if this proclivity for nucleophilic addition could be reduced, halogen-lithium exchange at C-2 would produce a lithiated 1-azafulvene functionally equivalent to a 5ilithiopyr-role-2-carboxaldehyde derivative.…”
Section: Introductionmentioning
confidence: 99%
“…(202) 2-Methylpyrrole is formylated exclusively in the 5-position and, predictably, the 2-position of 3-methylpyrrole is more activated towards electrophilic attack than is the 5-position, such that 2-formyl-3-methylpyrrole and 2formyl-4-methylpyrrole are obtained in a ratio of 4 : 1. (205 " 207) 2,3-, 2,4-, 2,5-, and 3,4-Dimethylpyrrole and 3-ethyl-2,4-dimethylpyrrole are readily formylated under standard conditions/ 109,118,149,203,205,[203][204][205][206][207][208][209][210][211] b u t m o r e vigorous conditions are required to effect the formylation of 4,5-dimethyl-2-phenylpyrrole. Similarly, the formation of the 2-and 5-formyl compounds (F13) and (F14) in a ratio of 4 : 1 and of the 3-and 4-formyl compounds, (F15) and (F16), also in a ratio of 4 : 1, reflect the relative steric effects of the a-and ß-substituents, respectively.…”
Section: C-acylation Reactionsmentioning
confidence: 99%
“…(83b,139) Vilsmeier-Haack formylation of pyrroles substituted with two electronwithdrawing groups presents no difficulties. (205) Although 3-nitropyrrole is formylated in good yield to give 4-nitro-2formylpyrrole, 2-nitropyrrole has been reported to be unreactive under Vilsmeier-Haack conditions. (213 ' 220) However, the attempted formylation of ethyl 3-acetyl-4methylpyrrole-2-carboxylate (F17) resulted in the formation of (F18).…”
Section: C-acylation Reactionsmentioning
confidence: 99%